John of God the globalization of Brazilian faith healing - Rocha, Cristina (New York, NY Oxford University Press, 2017)
This work investigates the growing number of Western followers of John of God, a faith healer who has drawn hundreds of thousands of people, including Oprah Winfrey, to his healing center in Brazil by purportedly performing miraculous surgeries on people with a kitchen knife and no anesthetics
Includes bibliographical references and index
Previously issued in print: 2017
Zielgruppe - Audience: Specialized
Keywords: Faria, João Teixeira da -- 1942-; Spiritual healing and spiritualism; Faria, João Teixeira da ; 1942-